A Modified Chemical Imaging Sensor System for Real‐Time pH Imaging of Accelerated Crevice Corrosion of Stainless Steel. Issue 15 (17th April 2018) - Miyamoto, Ko‐ichiro; Sakakita, Sakura; Werner, Carl Frederik; Yoshinobu, Tatsuo
Abstract : The measurement system of a chemical imaging sensor is combined with the circuitry for polarization of a metal test piece. The surface of the metal test piece is brought into contact with the sensor surface forming a crevice of about 12 µm width. The course of initiation and propagation of corrosion are observed as serial images of pH in the crevice. A local change of the pH value down to 2 is observed in synchronization with the change of the anodic current. Abstract : In situ visualization of pH change in the course of crevice corrosion is presented here. The pH distribution in the vicinity of a test piece of stainless steel under potentiostatic polarization is measured by a chemical imaging sensor. In synchronization with the increase of the corrosion current, the pH value drops to about 2 at the location where corrosion is initiated.